PENGELOLAAN PEMBELAJARAN IPS TERPADU BERBASIS KURIKU LUM TINGKAT SATUAN PENDIDIKAN (KTSP) (STUDI SITUS DI SMP NEGERI 1 WONOGIRI) - SETYOWATI , SETYOWATI (2011)
In this research is generally puspossed to describe the management of the Integrated Social Sciences instructional based The Eduction Unit Level Curriculum (KTSP) (Site Study at SMP Negeri 1 Wonogiri. Specifically the focus of the research is the things selated to the management of the Integrated Social Sciences instructional based The Education Unit Level Curriculum (KTSP) to describe; 1) the characteristics of the Integrated Social Sciences instructional based The Educational Unit Level Curriculum (KTSP), 2) the characteristics of the Integrated Social Sciences instructional lay out based KTSP, and 3) the characteristics of students activity in the Integrated Social Sciences instructional based KTSP. This is a qualitative research with ethnographic design, The site of the research is SMP Negeri 1 Wonogiri. The sources of are taken informant, event and documents. The informants in this study are the headmaster, the deputy headmaster of the school curriculum and Social science teachers. Events in this study are things related to Social Science Intregated Learniing management Based Kurikulum Tingkat Satuan Pendidikan (KTSP), the documents in this research are the documents related to Social Science Integrated Learning management Based Kurikulum Tingkat Satuan Pendidikan (KTSP). The data collected were analyzed by analysis of the interactive model that includes data collection, data reduction, data representation and inference. The result of the research can be concluded that. 1) The interaction in Integrated Social Sciences learning can be better if between the teacher and student understand their own role, teacher's role is as an educator and student's role is as a learner, so there will be a good interaction in learning process, 2) The lay out of Integrated Social Sciences learning will be more interesting if it is performed by using a certain approach and method which is appropriate with the materials taught, and the teacher is able to use the media well, 3) The student activity in the Integrated Social Sciences learning will be more optimal if the material can motivates and stimulates the students' interest to study.